Alleviate cascade with fault pair in interdependent smart grid: a communication view. (3rd April 2018) - Wang, Kaixuan; Zeng, Qingtao; Xing, Ningzhe; Guo, Shaoyong
Abstract: Smart grid has brought an innovation of traditional power. Smart grid, which couples communication network with power network, tends to cascade because of the heterogeneous coupling. Some research works have focused on external network features to mitigate the cascade, such as vulnerability and reliability. These studies, however, put less attention to an internal fault and fail to grasp cascading details. In this paper, we propose a pairwise scheme to investigate fault propagation in an interdependent network. The interdependent network model is built to characterize the fault cascade. Then, we leverage fault pair and analyze the necessary condition of the cascade. To alleviate cascading, we resort to find the minimized node set with constraints from a communication perspective. Further, the heuristic DCDR algorithm is proposed to hold the necessary redundant node set to relieve cascade. Extensive experiments not only illustrate the effectiveness of our approach on networks with different parameters, but also highlight some important observations which may give more insight to interdependent networks.